Discriminating between the dissociative photoionization and thermal decomposition products of ethylene glycol by synchrotron VUV photoionization mass spectrometry and theoretical calculations. Issue 43 (1st November 2022) - Wang, Hong; Guan, Jiwen; Gao, Jiao; Li, Yanbo; Zhang, Jinyang; Shan, Xiaobin; Wang, Zhandong
Abstract : Landscape of dissociative photoionization and thermal decompositions of ethylene glycol. Abstract : Understanding the combustion chemistry of biofuel compounds is of great importance in the intelligent selection of next-generation alternative fuels. Ethylene glycol (C6 H10 O2 ) is a prototypical representative of potential biofuels. In this work, the thermal decompositions along with the dissociative ionization of ethylene glycol are studied by synchrotron VUV photoionization mass spectrometry. As a part of the dissociative ionization study, the appearance energies of seven fragments are measured. Using the theoretical calculation results, the possible formation channels of these fragments are proposed. In particular, the productions of CH3 OH + and CH3 OH2 + are suggested to be from the isomerization/dissociation process, where double proton transfer processes are highlighted. Using a tunable VUV source, the high-temperature pyrolysis products of ethylene glycol are differentiated from the dissociative ionization products. Specifically, two isomeric products vinyl alcohol and acetaldehyde by H2 O elimination are obtained. Formaldehyde and methanol from direct C–C bond cleavage are identified. The fragmentations of fragile radicals such as hydroxymethyl, methoxy and ethoxy are used to explain the missing products from the direct C–C and C–O bond dissociation reactions. There is no experimental evidence for the occurrence of the H and H2 elimination reactions which may have not been accessed under the present temperature conditions.